Implementation of Manager Performance Decision Support System Using the Simple Additive Weight Method - Ahmad Faraz Mutaqin; Purnomo Sidiq; Yopi Nugraha (Institut Pendidikan Indonesia, 2020)
Abstract: In the development of the role and results, the quality of human resources is one of the supporting factors to increase the productivity of the performance of a company/institution. Then highly competent human resources can support the level of performance, with an integrated performance appraisal system of employee performance appraisal, will provide opportunities and reinforcement in determining the goals of an organization, with the system it is known the achievements of each employee, both in improving the quality of employees' abilities for consideration in achieving promotions in determining the best employees. With a method approach in a good decision support system, it is hoped that decision making for leaders for managers can be clearly illustrated with work abilities according to the criteria in assessing performance values, discipline, personality, creativity, activeness and caring, which will later use the Simple method approach. Additive Weight, where this method is a weighted numbering method or a method that provides certain criteria that have a weighted value for each criterion, so that from the sum of these weights the ranking results will be obtained as a final assessment for leaders in structured decision making in development. employee career. Keywords: DSS, SAW, Manager Abstrak: Dalam perkembangan peranan dan hasil kualitas sumber daya manusia merupakan salah satu faktor penunjang untuk meningkatkan produktivitas kinerja suatu perusahaan/instansi. Maka sumber daya manusia yang berkompetensi tinggi dapat mendukung tingkat kinerja, dengan penilaian kinerja terintegrasi sistem penilaian kinerja karyawan, akan memberikan kesempatan dan penguatan dalam penentuan tujuan suatu organisasi, dengan sistem tersebut diketahui prestasi yang dicapai setiap karyawan, baik dalam peningkatan kualitas kemampuan karyawan untuk pertimbangan dalam pencapaian promosi dalam menentukan karyawan terbaik. Dengan pendekatan metode dalam sistem pendukung keputusan yang baik, diharapakan penentuan keputusan untuk para para pimpinan untuk para manajer dapat tergambar dengan jelas dengan kemampuan kerja sesuai kriteria dalam penilaian nilai kinerja, kedisplinan, kepribadian, kreativitas, keaktifan dan kepedulian, yang nantinya dengan pendekatan metode Simple Additive Weight, dimana metode ini merupakan metode pembilangan terbobot atau metode yang memberikan kriteria-kriteria tertentu yang memiliki bobot nilai masing-masing kriteria, sehingga dari hasil penjumlahan bobot tersebut akan diperoleh hasil perangkingan sebagai penilaian akhir untuk para pimpinan dalam pengambilan keputusan yang terstruktur dalam pengembangan karier karyawan. Kata kunci: SPK, SAW, SDM , Manager